The effect of ultraviolet-light exposure on ornithine decarboxylase (ODC1) and pigmentation in human skin cells - Ong, Yee Hwee (2019)
Environmental stressors like UV light cause cellular damage that triggers protective and repair mechanisms. A common photo-protective response is an upregulation of skin pigmentation. This results in the formation of melanin caps around the nucleus of skin cells, which protect against DNA damage. Polyamines are ubiquitous, low-molecular-weight polycations known to regulate cell proliferation and survival; and they were recently found to mediate pigmentation. However, the exact mechanism by which polyamines promote pigmentation is not established. We hypothesized that ornithine decarboxylase (ODC1), a key polyamine biosynthesis enzyme, is involved in UVB-induced skin pigmentation, and that inhibition of ODC1 will prevent UVB-induced skin pigmentation. Using putrescine-treatment on cell cultures, polyamines were confirmed to promote melanogenesis. Western blot analysis then revealed that ODC1 protein levels in skin cells, melanocytes and keratinocytes, increase proportionally with UVB exposure. We then tested whether ODC1 inhibition impedes UVB-induced pigmentation using melanocyte and keratinocyte co-culture assays. However, the results were not statistically significant and more replicates are needed to obtain a conclusive result. Preliminary data show that polyamines can induce pigmentation in human skin but its role in UVB-induced skin pigmentation needs to be further explained.